Social Networking Website Gathers Individuals for a Social cause - A Study on Facebook Events - Kavitha, G (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Communication between the individual and the society becomes easy and faster with the world’s largest encyclopedia which is called as Internet. Social media networking websites and applications paved way to share one’s own feelings and emotions to the known and unknown faces with a single click. Whether it is personal or social, messages are getting posted not only through computers but also through their updated android mobile phones. Social networking website is used to linkup the likeminded people and gathers them for the social cause. Chennai Memes Facebook page events from the year 2016 till the mid of 2018 were taken for this study. This research will reveal the various types of events posted to gather people, the way how the message was communicated to the masses in a social media and the reason for posting the events. This study is basically exploratory in nature and followed mixed methodology. How to cite this article: Kavitha G. Social Networking Website Gathers Individuals for a social cause - A Study on Facebook Events. J Adv Res Jour Mass Comm 2018; 5(4): 148-153. DOI: https://doi.org/10.24321/2395.3810.201830